FAKTOR –FAKTOR RISIKO YANG BERPENGARUH TERHADAP KEJADIAN HIV dan AIDS DI SEMARANG DAN SEKITARNYA - Tuti Susilowati (Jurnal Komunikasi Kesehatan, 2010)
Background : HIV/AIDS is a global problem, it is essential immediately overcame and havehigh mortality. AIDS caused by HIV virus. The prevalence of HIV/AIDS cases in Indonesiahas increased as well in Semarang. The data in Semarang shows the cumulative number everin the caring of HIV/AIDS in July 2009 was 607 cases, 478 cases had ART treatment. Peopleliving with HIV who had reinforced until July 2009 was 281 cases. The amount of virus inagent determining transmission, while the infection depends on the disease stages. Thedisease is not a cure, the vaccine is not yet available.Objectives: Getting information of risk faktors that affect the incidence of HIV/AIDS and itsdevelopment in the Semarang area.Method: Type of analytical observational research, Case Control method. The case was allpatients with all age groups who have been diagnosed had HIV/AIDS in Dr. Kariadi GeneralHospital especially taking medication regularly both in outpatient or inpatient. The controlwas blood donors from the Red Cross Branch Semarang. Number of samples was 76 as casesand 76 as controls. The samples tested qualitatively.Results: Risk faktors affecting the incidence of HIV/AIDS: History of disease (STD) OR:2,676 (95% CI 1,252-5,720, p value 0.01). The history of disease in family who hadHIV/AIDS OR: 2,592 (95% CI 1,078-6,233, p: 0.033). Level of education OR: 4,709 (95%CI 1,078-10,474 p: 0.001). Status of injecting drug use/IDU OR: 4,515 (95% CI 1,940-10,507p: 0.001).. While that does not affected was history of previous disease (there are sexuallytransmitted diseases, organ transplants), gender, level of knowledge, socio-economiccondition and BMI, blood donor status, The status have received a blood transfusion, initialsex status, demographical residential/domicile. have the cultural background of more thanone partner.Conclusion: The risk faktors that proved to affected to incidence of HIV/AIDS including:STD, family history of disease in had HIV/AIDS, education level, status of injecting druguse/IDU, the status had received blood transfusions, embracing the cultural background ofmore than one partner, the behaviors that have risk of HIV/AIDS transmission is potentiallyoccurred.Suggestion: It is recommended to be re-screened for the potential risk of HIV and AIDSincidence because basically awareness for those at risk still need special attention. Handlingof HIV and AIDS at the level of basic services should be noted that this case does not becomean epidemic.